Participacão do transporte de acetilcolina, do cálcio intracelular e do colesterol de membrana no ciclo de vesiculas sinapticas em juncãoneuromuscular - Ernani Aloysio Amaral (2010)
Synaptic vesicles recycling is essential for the maintenance ofneurotransmission by preventing the collapse of synaptic function. In this work, three important aspects of the synaptic vesicle cycle were investigated in preparations of mouse and frog neuromuscular junction: 1) the consequences of alterations in the expression of the vesicular acetylcholine transporter (VAChT) over synaptic vesicle cycle; 2) the involvement of intracellular calcium stores on the exocytosis evoked by the cardiotonic glycoside ouabain; and 3) the role of membrane cholesterol on the exo/endocytosis of synaptic vesicle. The results presented here indicated that the decrease in VAChT expression cause no compensatory alteration in the number and area of motor terminals at diaphragms of VAChT knockdown mice. Moreover the number of synaptic vesicles able to recycle and the steps of exo/endocytosis seemed tobe preserved in knockdown homozygote animals. However the absence of VAChT expression caused an increase in the number and area of motor terminals at diaphragms of knockout mice. Data relating to ouabain-induced exocytosis showed that this glycoside promotes vesicle release recruiting calcium stored at endoplasmic reticulum and mitochondria through ryanodine receptors and mitochondrial Na+/Ca2+ exchanger, respectively. As for the role of membrane cholesterol on synaptic vesicle cycle, the results indicated that cholesterol removal increased spontaneous vesicle release, modified amplitude and kinetics parameters of spontaneous events but inhibited K+-evoked exocytosis. All aspects investigated in this work can contribute to broaden theknowledge about the cholinergic system and neurotransmission. Perhaps, in the future, the data presented here could subsidize pharmacological interventions on disturbs of peripheral and central synapses.